Ru-Sn-B/Al2O3 Catalysts for Selective Hydrogenation of Methyl Oleate: Influence of the Ru/Sn Ratio - Sánchez, María Amparo (2015)
This study focuses on the influence of the Ru/Sn ratio on the catalytic hydrogenation of methyl oleate to oleyl alcohol using Ru-Sn-B catalysts, notably on the catalytic activity and selectivity. Sn addition acts positively over the oleyl selectivity by reducing therates of C=O and C=C saturation but also decreases the global activity.The catalyst with the highest activity and selectivity towards oleyl alcohol is Ru(1%)-Sn(2%)-B/Al2O3. At a low Sn loading (0.5%) the catalyst has high activity for hydrogenation of the carbonylgroup and the carbon-carbon double bond. As a consequence stearyl alcohol is produced with high yield. At a high Sn content (4%) the catalyst has lower selectivity to oleyl alcohol due to its low capacity for hydrogenating the carbonyl group. However it has enough activity for hydrogenating the C=C double bonds to produce the saturated methyl ester.